Психологічні типи правоохоронців – дрібних корупціонерів - Ларіонова, І. Т.; Larionova, I. T.; Колесніченко , О. С.; Kolesnichenko, O. S. (Теоретичні і прикладні проблеми психології та соціальної роботи. - 2023. - № 1. - С. 84-97, 2023)
Стаття містить результати оригінального емпіричного дослідження схильних до дрібної корупції правоохоронців, в якому реалізований типологічний підхід до особистості. Дослідження проведено на матеріалі результатів психодіагностики 87 військовослужбовців Національної гвардії України, під час професійно-психологічного відбору на вищі посади та посади, що передбачають облік товарно-матеріальних цінностей, і які проходили обстеження за допомогою поліграфа. Використано результати професійно-психологічного відбору досліджуваних, які у подальшому піддавались процедурі кластерного аналізу.

The article contains the results of original empirical research of law enforcement officers inclined to minor corruption, which was implemented by typological approach to a personality. The research was based on the psychodiagnostics results of 87 servicemen of the National Guard of Ukraine which was carried out with use of polygraph during the professional and psychological selection for higher positions and positions which includes material responsibility. The results of professional and psychological selection of candidates was used by further cluster analysis procedure. It has been defined that representatives of first type of minor military corruptors are inclined to demonstrate their superiority, exceptional knowledge and is based on undeveloped desire to work on themselves, allows other people to manipulate them, involve them and use as a tool in illegal activities. They probably find it convenient to obtain illegal benefits appeasing themselves by thoughts that they are not responsible for activities, which were not initiated by them (e.g. compliance of higher command orders). skills over others, their excessive demanding of themselves and others. Their intolerance to everything that differs from their understanding of true things, narrow professional perception of relationship and reality, severity and negative mood forces those who doesn’t meet these requirements to appease them. Representatives of the first type accept “gifts” and confuse them with manifestation of respect as well as recognition of their “uniqueness” as professional in certain fields. They trade their favor and commercialize their services as a specialist in certain field using the tools of unfair competition. The second type of minor military corruptor has been characterized. These are representatives of a new, young generation of military personnel who are sufficiently erudite, professionally motivated, confident in themselves and their professional training. However, due to their tolerance and adaptability they perceive the phenomenon of corruption as objectively given and something that just has to be accepted. They are tolerant to corruption and in some time consider it as an option for achievement. They allow making them a part of corruption. The third type representatives of minor military corruptors are not distinguished by specific abilities and sincere love to the profession of a serviceman of the NGU. However, being a part of the social group of law enforcement officers, particularly, the one who are endowed with formal power allows them to feel themselves as respected and significant people. Their low professional identity, which

Статья содержит результаты оригинального эмпирического исследования подверженных мелкой коррупции правоохранителей, в котором реализован типологический подход к личности. Исследование проведено на материале результатов психодиагностики 87 военнослужащих Национальной гвардии Украины, во время профессионально-психологического отбора на высшие должности и должности, предусматривающие учет товарно-материальных ценностей и проходивших обследование с помощью полиграфа. Использованы результаты профессионально-психологического отбора испытуемых, которые в дальнейшем подвергались процедуре кластерного анализа.
Psychological types of law enforcement officers – petty corruptors
Keywords: психологічні типи; psychological types; психологические типы; працівники правоохоронних органів; law enforcement officers; работники правоохранительных органов; корупція; corruption; коррупция; військовослужбовці Національної гвардії України; servicemen of the National Guard of Ukraine; военнослужащие Национальной гвардии Украины